THU0384 Performance of The Asas Classification Criteria for Axial and Peripheral Spondyloarthritis – A Systematic Literature Review and Meta-Analysis. (15th July 2016) - Sepriano, A.; Rubio, R.; Ramiro, S.; Landewé, R.; van der Heijde, D.
Abstract : Background: The Assessment of SpondyloArthritis international Society (ASAS) has developed and validated classification criteria for axial spondyloarthritis (axSpA) and peripheral SpA (pSpA). Following their release, the ASAS criteria have been "challenged" in different cohorts, thus warranting a review of the so-far accumulated evidence on the criteria validity and applicability. Objectives: To summarize the evidence on the performance of the ASAS classification criteria for axSpA (also imaging and clinical arm separately), pSpA and the entire set of SpA, when tested against the Rheumatologist's diagnosis ("reference standard"). Methods: A systematic literature review was performed to identify eligible studies. Only studies with full-text available were included and, thereafter, raw data was obtained from the authors of the selected publications. A meta-analysis was performed to obtain pooled estimates for sensitivity, specificity, positive (LR+) and negative (LR-) likelihood ratios, by fitting random effects models. With a series of sensitivity analyses we assessed the possible effects of: i) target population (original validation study inclusion criteria vs different inclusion criteria); iii) setting (hospital vs community); and iii) disease duration (<2 years vs ≥2 years). Results: Of the 1, 647 retrieved articles, 8 fulfilled the inclusion criteria (N=5, 042 patients). The entire set of the ASAS SpA criteria yielded a high pooled sensitivity (73%) and specificity (88%), but with limited available data (Table ). Similarly good results were found for the axSpA criteria (sensitivity: 82%; specificity: 88%) in a larger number of studies. Splitting the axSpA criteria in "imaging arm only" and "clinical arm only" resulted in much lower sensitivity (30% and 23% respectively) but retaining very high specificity (97% and 94% respectively). The "imaging arm only" compared to the "clinical arm only" had a much higher LR+ (9.6 vs 4.5, respectively). The pSpA criteria were less tested than the axSpA and have shown a similarly high pooled specificity (87%) but lower sensitivity (63%). Sensitivity analyses yielded consistently good results for the axSpA criteria (sensitivity (range): 78% - 86%; specificity (range): 86% - 93%). For pSpA there were few studies therefore hampering sensitivity analyses. Conclusions: Accumulated evidence from more than 5, 000 patients confirms the good performance of the various ASAS SpA criteria as tested against the Rheumatologist's diagnosis. The clinical and imaging arm have high specificity but lack sensitivity if applied separately, indicating that the full set of axSpA criteria is the preferred set. Disclosure of Interest: None declared